The endogenous cellular protease inhibitor SPINT2 controls SARS-CoV-2 viral infection and is associated to disease severity - Ramirez, Carlos; Kee, Carmon; Sharma, Ashwini Kumar; Thomas, Leonie; Schmidt, Florian I.; Stanifer, Megan; Boulant, Steeve; Herrmann, Carl (PLoS pathogens, 2021)
COVID-19 outbreak is the biggest threat to human health in recent history. Currently, there are over 1.5 million related deaths and 75 million people infected around the world (as of 22/12/2020). The identification of virulence factors which determine disease susceptibility and severity in different cell types remains an essential challenge. The serine protease TMPRSS2 has been shown to be important for S protein priming and viral entry, however, little is known about its regulation. SPINT2 is a member of the family of Kunitz type serine protease inhibitors and has been shown to inhibit TMPRSS2. Here, we explored the existence of a co-regulation between SPINT2/TMPRSS2 and found a tightly regulated protease/inhibitor expression balance across tissues. We found that SPINT2 negatively correlates with SARS-CoV-2 expression in Calu-3 and Caco-2 cell lines and was down-regulated in secretory cells from COVID-19 patients. We validated our findings using Calu-3 cell lines and observed a strong increase in viral load after SPINT2 knockdown, while overexpression lead to a drastic reduction of the viral load. Additionally, we evaluated the expression of SPINT2 in datasets from comorbid diseases using bulk and scRNA-seq data. We observed its down-regulation in colon, kidney and liver tumors as well as in alpha pancreatic islets cells from diabetes Type 2 patients, which could have implications for the observed comorbidities in COVID-19 patients suffering from chronic diseases. Author summary Since early 2020, the world is facing a unique pandemic situation triggered by the appearance of a new coronavirus, Sars-CoV-2. While it shares similarities with previous coronaviruses, it shows some unique features, which requires in-depth investigations to understand its mechanisms of action, in particular the type of cells which can be infected, and the mechanism of cellular entry. We describe a new important actor which plays a decisive role in the entry of the virus into the cell. The serine protease inhibitor SPINT2 inhibits the well described serine protease TMPRSS2, and we show that inhibiting or overexpressing this gene leads to an increase, respectively a strong decrease of the number of infected cells. Intriguingly, this gene has been described in the context of diseases which are known to be comorbid with COVD19, for example Type 2 diabetes and several malignancies. Using published datasets, we show that in these comorbid diseases, SPINT2 is downregulated, which might lead to an increase of the infectivity of cells in disease-tissues such as endocrine cells of diabetic patients or cells from tumor tissues.